A New Member of Electrocatalysts Based on Nickel Metaphosphate Nanocrystals for Efficient Water Oxidation. Issue 5 (11th December 2017) - Huang, Jianwen; Sun, Yinghui; Zhang, Yadong; Zou, Guifu; Yan, Chaoyi; Cong, Shan; Lei, Tianyu; Dai, Xiao; Guo, Jun; Lu, Ruifeng; Li, Yanrong; Xiong, Jie
Abstract: High‐performance electrocatalysts are desired for electrochemical energy conversion, especially in the field of water splitting. Here, a new member of phosphate electrocatalysts, nickel metaphosphate (Ni2 P4 O12 ) nanocrystals, is reported, exhibiting low overpotential of 270 mV to generate the current density of 10 mA cm −2 and a superior catalytic durability of 100 h. It is worth noting that Ni2 P4 O12 electrocatalyst has remarkable oxygen evolution performance operating in basic media. Further experimental and theoretical analyses demonstrate that N dopant boosts the catalytic performance of Ni2 P4 O12 due to optimizing the surface electronic structure for better charge transfer and decreasing the adsorption energy for the oxygenic intermediates. Abstract : A new type of nickel metaphosphate nanocrystal electrocatalyst exhibits high oxygen evolution reaction performance due to exposed active facets. Experimental and theoretical analyses demonstrate that N doping further boosts the catalytic activity via modifying the electronic structure and facilitating the formation of OO bonding.